Compensatory Control and Its Implications for Ideological Extremism. (9th September 2013) - Kay, Aaron C.; Eibach, Richard P.
Abstract : This article outlines and reviews evidence for a model of compensatory control designed to account for the motivated belief in personal and external sources of control. In doing so, we attempt to shed light on the content and strength of ideologies, including extreme libertarian, nationalist, socialist, and religious fundamentalist ideologies. We suggest that although these ideologies differ in their content they commonly function to provide people with a sense of control over otherwise random events. We propose that extreme ideologies of personal control (e.g., libertarianism) and external control (e.g., socialism, religious fundamentalism) are equifinal means of meeting a universal need to believe that things, in general, are under control—that is, that events do not unfold randomly or haphazardly. We use this model to explain how the adoption and strength of ideologies of personal and external control may vary across temporal and sociocultural contexts.